Anodic oxidation of bisphenol A by different dimensionally stable electrodes - Can, Orhan T.; Tutun, Muhammed M.; Keyikoglu, Ramazan (Iwa Publishing, 2021)
Bisphenol A (BPA) is a known endocrine disrupter and was detected in surface waters. We investigated the mineralization of BPA by electrochemical oxidation. Six different types of electrodes, including the boron-doped diamond (BDD), platinum (Pt), and mixed metal oxide (MMO) electrodes; RuO2-IrO2, RUO2-TiO2,IrO2-Ta2O5, and Pt-IrO2, were compared as the anode material. Total organic carbon (TOG) was analyzed to monitor the mineralization efficiency of BPA. BDD achieved 100% BPA mineralization efficiency in 180 min and at a current density of 125 mA/cm(2), whereas the TOG removal efficiency of Pt was 60.9% and the efficiency of MMO electrodes ranged between 48 and 54%. BDD exhibited much lower specific energy consumption, which corresponds to a lower energy cost (USD63.4 /kg TOG). The effect of operational parameters showed that the BDD anode was much more affected by the current density, initial BPA concentration, and electrolyte concentration than the other parameters such as the stirring speed and interelectrode distance.
Keywords: boron-doped diamond; electrochemical oxidation; mineralization; mixed metal oxide anodes; specific energy consumption